2012
DOI: 10.1016/j.techfore.2011.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Multi-dimensional struggles in the greening of industry: A dialectic issue lifecycle model and case study

Abstract: This paper aims to make two conceptual contributions to the greening of industry literature. Firstly, we propose that the greening process can be conceptualized as an issue lifecycle dynamics with multi-dimensional struggles between 'greening' pressures and industry response strategies. To capture the endogenous dynamics, we develop a Dialectic Issue LifeCycle model with five phases, which conceptualize how these struggles play out over time. Secondly, we propose that issue lifecycle dynamics are also influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
111
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(114 citation statements)
references
References 34 publications
3
111
0
Order By: Relevance
“…Examples from other contexts point towards things not being so simple however. This factor of social movements and 'framing struggles' is well explored in wider literatures concerning conditions for destabilisation of sociotechnical regimes (Geels & Verhees, 2011;Penna & Geels, 2012;Turnheim & Geels, 2012). And in the above comparison of the cases of nuclear incumbency in the UK and Germany, this factor seems strongly in alignment with the observed trend.…”
Section: Summary Of Key Patternsmentioning
confidence: 68%
“…Examples from other contexts point towards things not being so simple however. This factor of social movements and 'framing struggles' is well explored in wider literatures concerning conditions for destabilisation of sociotechnical regimes (Geels & Verhees, 2011;Penna & Geels, 2012;Turnheim & Geels, 2012). And in the above comparison of the cases of nuclear incumbency in the UK and Germany, this factor seems strongly in alignment with the observed trend.…”
Section: Summary Of Key Patternsmentioning
confidence: 68%
“…A fourth possibility is that public attention and concern increase again in a few years' time, which creates pressure on policymakers to take bold actions. Such oscillations are not uncommon in issue-attention cycles (Penna and Geels, 2012). Future increases in public attention may be related to new scientific findings (e.g.…”
Section: Resultsmentioning
confidence: 95%
“…Gough and Meadowcroft (2011: 494) also suggest that fiscal and economic problems have returned as central political issues, and warn that this may hinder or delay sustainability transitions: "The real worry is that a serious mitigation response will be delayed for one or more decades." In a historical study of air pollution, Penna and Geels (2012) found that the 1973 oil crisis and ensuing recession caused a steep decrease in public attention to the issue (Figure 1), followed by stagnation in the implementation of the 1970 Clean Air Act. The 1979 oil crisis and the recession of the early 1980s caused a further 5 decline in attention and stalled political action on air pollution until 1990.…”
Section: Introductionmentioning
confidence: 99%
“…to low carbon energy; from combustion and purely private mobility to electric vehicles and shared mobility systems; as well as from conventional consumption goods to environmentally friendly and fairtrade products (e.g. Geels 2012; Penna and Geels 2012). Such strategic renewal, as opposed to operational optimisation, requires long-term investments without an ultimate guarantee of success.…”
Section: More Recent Sbsc Architectures Mostly Ignoredmentioning
confidence: 99%
“…Even though Kaplan and Norton's original conception of the BSC's learning and growth perspective was intended to provide space for such learning processes, it may be very difficult to realise this potential in a hierarchy dominated by top-level financial goals. In contrast, semi-hierarchical BSCs may foster the incorporation of a 'future dimension' into performance measurement systems (Maltz et al 2003, p. 191) and thus enable ambidextrous organisations with the capability to simultaneously manage incremental and radical change processes within the same organisation (Tushman and O'Reilly 1996;Raisch et al 2009). …”
Section: More Recent Sbsc Architectures Mostly Ignoredmentioning
confidence: 99%